G17 Transforming the design of a children's emergency department – simulation as a powerful service development tool. (7th April 2014) - Hyde, P; Sykes, K; Pryde, K; Smoult, H; Eddie, M; Barling, J; Halford, S; Crouch, R; Battrick, C; Hammett, O; Bennett, T; Hamilton, C; et al.
Abstract : Aim: To utilise large scale simulation to assess the full system functioning of a children's emergency department prior to actually constructing the building. The simulation aimed to identify the impact of physical structure, patient pathways and staffing levels on patient care and experience, departmental efficiency and safety. The simulation was timed to enable the lessons learnt to inform the departmental design, before the final stages of the build commenced. Methods: A life size temporary model of the proposed children's emergency department was built, with full size walls, equipment and facilities mirroring the proposed layout. The department was staffed with a full compliment of nurses, doctors and therapists, who over a 5 h period treated 53 child simulated patients and accompanying supervising adults for a range of simulated illness and injury. The simulated patients reflected a typical Saturday evening case mix and the entire patient journey from reception to admission or discharge was simulated in real time. Verbal and written feedback was captured from patients, carers, clinical staff and subject matter experts. Feedback was presented at follow up multi-professional discussion sessions to enable functional utilisation of the data. Results: Data regarding the departmental flow of patients, therapies provided to patients and timeliness of treatment, in addition to multi-modal feedback, demonstrated clear structural, functional and staffing challenges within the proposed design. Conclusion: The multi-modal simulation feedback catalysed a redesign of the internal space, patient flow and clinician utilisation within the proposed children's emergency department. These changes were implemented prior to building the actual department; preventing exposure of real patients to this learning curve. A first for the NHS, the project has demonstrated that design and quality improvement of complex systems can be achieved using large-scale simulation. Simulated child patients brought the clinical space to life, powerfully drew staff into the simulation and provided the child's perspective on issues such as confidentiality; generating functional information that cannot be obtained from paper modelling. The project demonstrates how staff, children and families can contribute meaningfully to the design of clinical spaces within the NHS.